FABRIKASI DAN PENGUJIAN TARIK PIPA KOMPOSIT BERPENGUAT SERAT WOL DENGAN ADITIF PARTIKEL MONTMORIILLONITE - Ibrahim Tri Statistianto; Agus Triono (ROTOR, 2016)
Composite is one kind of material created by the merger of two or more kinds of materials that have different properties into one new materials with different properties. Composites are also widely used in the automotive industry. The use of composite particles of montmorillonite (MMT) is expected to contribute to the development of alternative materials made from clay. The purpose of this study was to determine the effect of particle size variation of the value of the tensile strength of the pipe Composite wool fibers with additive MMT particles, determine the effect of particle size variation of the morphology Composite pipe wool fibers with additive MMT particles after the drop test. The method used is the method of filament winding. For the testing standards used for tensile tests using ASTM D 2290. From the test results can be concluded that there are significant variations in particle size (MMT) against the tensile strength values with an average value of 20 = 49.08 MPa mesh, mesh 40 = 63.86 MPa, mesh 60 = 107.21 MPa, 138.78 MPa = 80 mesh, 100 mesh = 167.58 MPa, 120 = 190.05 mesh, mesh 150 = 210.89 MPa.